ANALISIS KESALAHAN SISWA DENGAN METODE NEWMAN DALAM MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Agnia Ilmiananda Putri; Iyan Rosita Dewi Nur (IKIP Siliwangi, 2022)
This study aimed to analyze student errors in solving a three-variable system of linear equations using Newman’s method. This type of research is descriptive qualitative research. The subject of this study was taken by purposive sampling technique and obtained five students who became the subject. The data collection techniques include test questions, interviews, and documentation. Data analysis techniques of this study include data reduction, data presentation, and conclusions. The results of this study can be concluded that the errors experienced by the five research subjects, namely: (1) In reading errors, comprehension errors, and transformation errors, students did not work on the questions given and did not understand the questions in the questions. (2) In the process skill error, students make errors in calculations, do not continue and do not know the steps in solving problems. (3) In enconding errors, the student does not show the final answer as asked in the question.